Financial Report Recording System At PT Asuransi Eka Lloyd Jaya - Tutut Alamin; Didik Sofian Haryadi; Titi Christiana (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to design a financial report recording system at PT Asuransi Eka Lloyd Jaya. By creating a financial reporting system, it is hoped that it will make it easier for the bookkeeping department to record financial data, as well as to make reports more quickly, which are used by the insurance company as a management tool for financial activities at PT Asuransi Eka Lloyd Jaya. Likewise, the aim of the research entitled